User Analysis of Halal Skincare Products: A Comparative Study of MS Glow and Scarlett Consumer Satisfaction - Idris Saleh; Lenni Mariyati (Institut Agama Islam Negeri Padangsidimpuan, 2022)
This study aims to determine whether there are differences in consumer satisfaction in using halal skincare products in the case studies of MS Glow and Scarlett. The background of this research is the competition in the cosmetics business in Indonesia which is experiencing significant developments. One of the cosmetic products that is developing and much-loved by the people of Indonesia is skincare products, this is indicated by the many different types of skincare on the market. Skincare is a series of activities that support healthy skin, increase self-confidence and make skin feel lighter. Competition between skincare brands indirectly affects every skincare company to maintain its market share. Every company is expected to be able to analyze what is needed by consumers so that consumers feel satisfied with the product. This research is a quantitative research with a comparative type or comparison. The data collection instruments used were interviews and questionnaires. Sampling using Purposive Sampling technique. The number of samples is 97 respondents. The analytical tools used are validity test, reliability test, normality test, homogeneity test and Independent Sample T Test. Based on the results of the study, it was obtained a significance value of 0.548, namely (0,548 0,1) then Ha was rejected and Ho was accepted. So it can be concluded that from the results of the Independent Sample T Test there is no difference in consumer satisfaction in using MS Glow and Scarlett halal skincare products.